Government Expenditure and Human Development in Indonesia - Johan Beni Maharda; Bunga Zharfa Aulia (Jambura Equilibrium Journal, 2020)
This study aims to estimate the association between government expenditure and human development index (HDI) in Indonesia. Due to inequal HDI attainment, this study focuses on 12 provinces which categorized as provinces with low level of HDI in Indonesia. This study employs fixed effect model (FEM) panel data analysis on provincial level datasets from 2010 to 2018. This study found that the increase of government expenditure on education significantly increases HDI, while government expenditure on health has no significant association with HDI. Major finding of the study highlights the role of gross regional domestic product (GRDP) per capita in increasing HDI on 12 provinces in Indonesia. Keywords: Government expenditure on education, government expenditure on health, HDI, FEM.